Pendidikan Kesehatan terhadap Peningkatan Pengetahuan tentang HIV/AIDS pada Remaja - Mesa, Nofita Dewi Kok; Watunglawar, Crystin Evangelin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to see the influence of the Influence of Health Education on Increasing Knowledge About HIV/AIDS in Adolescents at SMP X Sentani. The method used is a pre-experimental one-group pre-test and post-test without a control research design. The results of the study showed that there was a change in the average knowledge before and after being given an intervention in the form of health education (health counseling) with a mean difference of (+ 23.94) and a sig value (2-tailed) of 0.000 which means that there is an influence of health education on increasing students' knowledge about HIV/AIDS. The conclusion is that the intervention given in the form of health education has a significant influence on students. There is a difference in the average increase in students' knowledge before and after being given a health education intervention. Keywords: Health, Education, Knowledge